Clinical Outcomes in Hospitalized Patients with Decompensated Heart Failure: The Predictive Value of Precipitating Factors - Ragia Haduth (AlQalam Journal of Medical and Applied Sciences, 2025)
This study assesses the clinical outcomes in hospitalized patients with Decompensated Heart Failure (DHF); the predictive value of precipitating factors. We have analyzed the factors potentially which contribute to Heart Failure (HF) in hospitalization among 125 HF hospitalized patients with DHF in Albyda medical center. New onset HF and worsening HF conditions were observed across several health hypertension, atrial fibrillation, anemia, chronic obstructive pulmonary disease, stroke renal dysfunction, arrhythmia, ischemia. Ejection Fraction showed slight declines in both new onset (35.66 ± 8.021) and worsening (35.52 ± 8.12) scenarios. Mortality rates were starkly higher in worsening cases (90.4%) compared to new onset (9.6%). Among patients with reduced ejection fraction, longer hospital stays correlated with higher mortality rate. Hypertension, history of atrial fibrillation, COPD, stroke, arrhythmia, Patient with low EF longer hospital stay high mortality rate cases. تقيم هذه الدراسة النتائج السريرية لدى المرضى المقيمين في المستشفى المصابين بقصور القلب غير المعوض؛ والقيمة التنبؤية للعوامل المسببة. لقد قمنا بتحليل العوامل التي قد تساهم في قصور القلب في المستشفى بين 125 مريضًا مصابًا بقصور القلب غير المعوض في المستشفى في مركز البيضاء الطبي. لوحظت حالات قصور القلب الجديدة وتفاقم حالات قصور القلب في العديد من الحالات الصحية مثل ارتفاع ضغط الدم والرجفان الأذيني وفقر الدم ومرض الانسداد الرئوي المزمن والسكتة الدماغية واختلال وظائف الكلى وعدم انتظام ضربات القلب ونقص التروية. أظهرت نسبة القذف انخفاضًا طفيفًا في كل من سيناريوهات البداية الجديدة (35.66 ± 8.021) والتفاقم (35.52 ± 8.12). كانت معدلات الوفيات أعلى بشكل صارخ في الحالات المتفاقمة (90.4٪) مقارنة بالبداية الجديدة (9.6٪). بين المرضى الذين يعانون من انخفاض نسبة القذف، ارتبطت فترات الإقامة الطويلة في المستشفى بارتفاع معدل الوفيات. ارتفاع ضغط الدم، تاريخ من الرجفان الأذيني، مرض الانسداد الرئوي المزمن، السكتة الدماغية، عدم انتظام ضربات القلب، مريض لديه انخفاض كسر القذف ومدة إقامة أطول في المستشفى ومعدل وفيات مرتفع